DIFFERENT BODY FLUIDS: AN OVERVIEW - Gauttam, Narendra; Singh, Surya Pratap; Khinchi, M. P.; Nama, Nitin; Jain, Saloni (Asian Journal of Pharmaceutical Research and Development, 2017)
The focus of this article is to review the recent advances in proteome analysis of human body fluids, including plasma/serum, urine, cerebrospinal fluid, saliva, bronchoalveolar lavage fluid, synovial fluid, nipple aspirate fluid, tear fluid, and amniotic fluid, as well as its applications to human disease biomarker discovery. As a consequence the focus of the present review is to recognize the different body fluid compartments, to clinically assess the degree of dehydration, to know how the equilibrium between extracellular fluid and intracellular fluid is maintained, to calculate the effective blood osmolality and discuss both parenteral fluid requirments and repair.